Near-infrared shielding thermochromic intelligent window and preparation method thereof

By adopting the combination of hyperbolic metamaterial structure and VO2 metasurface layer in the smart window, the problems of high near-infrared transmittance and low mid-far infrared thermal radiation regulation amplitude are solved, and the infrared radiation regulation effect with low near-infrared band and large dynamic adjustable mid-far infrared band is achieved, which is suitable for the application of smart windows.

CN119502480AActive Publication Date: 2025-02-25SUZHOU LABORATORY

Patent Information

Application Number
CN202411683720.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-02-25
Estimated Expiration
2044-11-22

AI Technical Summary

Technical Problem

The existing thermally chromic smart windows have high near-infrared transmittance and low mid- and far-infrared thermal radiation regulation amplitude, making it difficult to effectively suppress the inward transmission of near-infrared energy.

Method used

A near-infrared shielded thermochromic smart window consisting of a base, a hyperbolic metamaterial structure, a first oxide dielectric layer and a VO2 metasurface layer are adopted from the bottom up. The hyperbolic metamaterial structure forms a four-layer structure through alternately arranged second oxide dielectric layer and metal reflective layer. The VO2 metasurface layer is composed of multiple W-doped VO2 micro-nano structural units. Through specific structural design and deposition technology, the near-infrared band low transmittance and large-scale dynamic adjustment of the medium and far-infrared band.

Benefits of technology

While the near-infrared band is low transmittance, the medium and far infrared band has large dynamic and adjustable infrared radiation regulation capabilities, which are suitable for intelligent window applications in automobiles and construction fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119502480A_ABST
    Figure CN119502480A_ABST
Patent Text Reader

Abstract

The invention discloses a near-infrared shielding thermochromic intelligent window and a preparation method thereof, and belongs to the field of radiation refrigeration and intelligent windows. The problems that an existing thermochromic intelligent window is high in near infrared transmittance and low in middle and far infrared heat radiation regulation and control amplitude are solved. A near-infrared shielding thermochromic intelligent window is composed of a substrate, a hyperbolic metamaterial structure, a first oxide dielectric layer and a VO2 metasurface layer in sequence from bottom to top. The preparation method comprises the following steps: 1, cleaning the substrate; 2, preparing a hyperbolic metamaterial structure; 3, preparing a first oxide dielectric layer; and 4, preparing the VO2 metasurface layer. The thermochromic intelligent window for near-infrared shielding and the preparation method thereof are provided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the fields of radiation cooling and smart windows. Background Art

[0002] With the continuous development of new energy vehicles, panoramic skylights are gradually replacing traditional car sunroof designs. However, the use of skylight glass can lead to excessive light and high temperatures inside the car. Traditional low-emissivity (Low-e) glass windows have high transparency in visible light and high reflectivity in the mid- and far-infrared regions, and have a certain radiative cooling effect, but they are mostly static thermal radiation regulation and lack adaptive temperature regulation functions, which can easily lead to overcooling at low temperatures. In recent years, by combining the optical properties of ITO glass and the thermo-induced phase change properties of VO2, smart windows such as VO2 / ZnSe / ITO and VO2 / HfO2 / SiO2 / ITO have been prepared, which have high visible light transmittance and dynamic regulation effects of mid- and far-infrared radiation. However, the mid- and far-infrared thermal radiation regulation amplitude is low, and they do not have good near-infrared shielding capabilities. Solar infrared energy is mainly concentrated in the range of 800nmnm to 2500nm. Therefore, in hot climates, it is even more necessary to suppress the inward transmission of near-infrared energy. Summary of the Invention

[0003] The present invention aims to solve the problems of existing thermochromic smart windows with high near-infrared transmittance and low mid- and far-infrared thermal radiation control range, and further provide a near-infrared shielding thermochromic smart window and a preparation method thereof.

[0004] A near-infrared shielding thermochromic smart window, which consists of a substrate, a hyperbolic metamaterial structure, a first oxide dielectric layer and a VO2 metasurface layer from bottom to top;

[0005] The hyperbolic metamaterial structure is a four-layer structure consisting of a second oxide dielectric layer and a metal reflective layer alternately arranged from bottom to top;

[0006] The VO2 super surface layer is composed of a plurality of W-doped VO2 micro-nano structural units, each of which is square in shape and has a side length of 1.5 μm to 4.5 μm. An array of a plurality of W-doped VO2 micro-nano structural units is arranged on the surface of the first oxide dielectric layer, with a surface coverage of 0.56 to 0.81, and a distance between adjacent W-doped VO2 micro-nano structural units of 0.5 μm to 1 μm.

[0007] In the W-doped VO2 micro-nanostructure unit, W accounts for 2% of the total number of W and V atoms.

[0008] A method for preparing a near-infrared shielding thermochromic smart window is carried out according to the following steps:

[0009] 1. Clean the substrate:

[0010] cleaning the substrate to obtain a pretreated substrate;

[0011] 2. Preparation of hyperbolic metamaterial structures:

[0012] Using DC magnetron sputtering technology, a second oxide dielectric layer and a metal reflective layer are alternately deposited on the pretreated substrate surface to form a four-layer structure, thereby obtaining a hyperbolic metamaterial structure.

[0013] 3. Preparation of the first oxide dielectric layer:

[0014] Using DC magnetron sputtering technology, a first oxide dielectric layer is deposited on the metal reflective layer on the top layer of the hyperbolic metamaterial structure;

[0015] 4. Preparation of VO2 super surface layer:

[0016] A VO2 layer is deposited on the first oxide dielectric layer using high-energy pulsed magnetron sputtering technology, and then post-annealing treatment is performed to obtain a planar multilayer film structure. A layer of photoresist is coated on the VO2 layer of the planar multilayer film structure and pre-baked. The photoresist is selectively exposed using ultraviolet photolithography technology, and then post-baked and developed. Reactive ion beam etching technology is then used for etching, and finally the photoresist is removed to obtain a VO2 super surface layer, thereby completing a preparation method for a near-infrared shielding thermochromic smart window.

[0017] The beneficial effects of the present invention are:

[0018] The present invention utilizes the unique optical properties of hyperbolic metamaterials to achieve low transmittance in the near-infrared band. At the same time, the high reflectivity of hyperbolic metamaterials in the mid- and far-infrared bands is utilized, combined with an infrared high-transmittance dielectric layer and a VO2 phase change layer to construct a Fabry-Perot resonant cavity, achieving large-scale dynamic adjustability in the mid- and far-infrared bands. Finally, by etching the surface VO2 to form a metasurface structure, the transmittance in the visible light band is effectively improved. At high temperatures, the localized surface plasmon resonance effect will further enhance the high-temperature infrared emissivity, thereby widening the infrared emissivity variation.

[0019] The near-infrared shielding thermochromic smart window described in the present invention has a visible transmittance of 28% to 54%, an average transmittance in the near-infrared band (0.8μm to 2.5μm) can be as low as 0.2% to 2.0%, and an emissivity change of 0.41 to 0.54 in the mid- and far-infrared (2.5μm to 25μm). The phase transition temperature is near room temperature, and it has excellent infrared radiation control capabilities, making it very suitable for applications in smart windows in fields such as automobiles and buildings.

[0020] The present invention is used for a near-infrared shielding thermochromic smart window and a preparation method thereof. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is a schematic structural diagram of the near-infrared shielding thermochromic smart window of the present invention, where 1 is the VO2 super surface layer, 2 is the first oxide dielectric layer, 3 is the metal reflective layer, 4 is the second oxide dielectric layer, and 5 is the substrate. DETAILED DESCRIPTION

[0022] Specific implementation method 1: Combination Figure 1 Specifically describing this embodiment, this embodiment is a near-infrared shielding thermochromic smart window, which is composed of a substrate, a hyperbolic metamaterial structure, a first oxide dielectric layer and a VO2 super surface layer from bottom to top;

[0023] The hyperbolic metamaterial structure is a four-layer structure consisting of a second oxide dielectric layer and a metal reflective layer alternately arranged from bottom to top;

[0024] The VO2 super surface layer is composed of a plurality of W-doped VO2 micro-nano structural units, each of which is square in shape and has a side length of 1.5 μm to 4.5 μm. An array of a plurality of W-doped VO2 micro-nano structural units is arranged on the surface of the first oxide dielectric layer, with a surface coverage of 0.56 to 0.81, and a distance between adjacent W-doped VO2 micro-nano structural units of 0.5 μm to 1 μm.

[0025] In the W-doped VO2 micro-nanostructure unit, W accounts for 2% of the total number of W and V atoms.

[0026] The membrane structure described in this embodiment includes a hyperbolic metamaterial layer, an oxide dielectric layer, and a phase change functional layer. The oxide dielectric layer is made of a material that exhibits excellent transmittance in the near-ultraviolet to infrared band.

[0027] This embodiment is based on hyperbolic metamaterials and Fabry-Perot (FP) resonant structures, combined with the VO2 thermoinduced phase change characteristics and surface plasmon resonance effect, to design and prepare a near-infrared shielding thermochromic smart window. While ensuring visible light transmittance, it effectively suppresses solar energy in the near-infrared band, and has the ability to adaptively adjust mid- and far-infrared radiation. In addition, in order to obtain better use effects, the VO2 phase transition temperature is regulated to near room temperature by W element doping. This design is expected to show great application potential in the fields of panoramic skylights, building exterior walls, and other fields of new energy vehicles. The method involved in the present invention is universal and practical.

[0028] The beneficial effects of this embodiment are:

[0029] This embodiment utilizes the unique optical properties of hyperbolic metamaterials to achieve low transmittance in the near-infrared band. At the same time, the high reflectivity of hyperbolic metamaterials in the mid- and far-infrared bands is combined with a high-infrared transmittance dielectric layer and a VO2 phase change layer to construct a Fabry-Perot resonant cavity, achieving large-scale dynamic adjustability in the mid- and far-infrared bands. Finally, by etching the surface VO2 to form a metasurface structure, the transmittance in the visible light band is effectively improved. At high temperatures, the localized surface plasmon resonance effect further enhances the high-temperature infrared emissivity, widening the infrared emissivity variation.

[0030] The near-infrared shielding thermochromic smart window described in this embodiment has a visible transmittance of 28% to 54%, the average transmittance in the near-infrared band (0.8μm to 2.5μm) can be as low as 0.2% to 2.0%, the emissivity change in the mid- and far-infrared (2.5μm to 25μm) reaches 0.41 to 0.54, the phase transition temperature is near room temperature, and it has excellent infrared radiation control capabilities, making it very suitable for the application of smart windows in fields such as automobiles and buildings.

[0031] Specific embodiment 2: This embodiment differs from specific embodiment 1 in that the substrate is made of quartz glass. Other aspects are the same as specific embodiment 1.

[0032] Specific embodiment 3: This embodiment differs from specific embodiment 1 or 2 in that the material of the first oxide dielectric layer and the second oxide dielectric layer is SiO2, ZrO2, HfO2, TiO2 or Al2O3. Other aspects are the same as specific embodiment 1 or 2.

[0033] Specific embodiment 4: This embodiment differs from specific embodiments 1 to 3 in that the material of the metal reflective layer is Ag or Au. Other aspects are the same as specific embodiments 1 to 3.

[0034] Specific embodiment 5: This embodiment differs from Specific embodiments 1 to 4 in that: the thickness of the first oxide dielectric layer is 500 nm to 1300 nm; the thickness of the second oxide dielectric layer is 100 nm to 150 nm; the thickness of the metal reflective layer is 10 nm to 18 nm; and the thickness of the VO2 supersurface layer is 20 nm to 60 nm. Other aspects are the same as Specific embodiments 1 to 4.

[0035] Specific embodiment 6: This embodiment provides a method for preparing a near-infrared shielding thermochromic smart window, which is carried out according to the following steps:

[0036] 1. Clean the substrate:

[0037] cleaning the substrate to obtain a pretreated substrate;

[0038] 2. Preparation of hyperbolic metamaterial structures:

[0039] Using DC magnetron sputtering technology, a second oxide dielectric layer and a metal reflective layer are alternately deposited on the pretreated substrate surface to form a four-layer structure, thereby obtaining a hyperbolic metamaterial structure.

[0040] 3. Preparation of the first oxide dielectric layer:

[0041] Using DC magnetron sputtering technology, a first oxide dielectric layer is deposited on the metal reflective layer on the top layer of the hyperbolic metamaterial structure;

[0042] 4. Preparation of VO2 super surface layer:

[0043] A VO2 layer is deposited on the first oxide dielectric layer using high-energy pulsed magnetron sputtering technology, and then post-annealing treatment is performed to obtain a planar multilayer film structure. A layer of photoresist is coated on the VO2 layer of the planar multilayer film structure and pre-baked. The photoresist is selectively exposed using ultraviolet photolithography technology, and then post-baked and developed. Reactive ion beam etching technology is then used for etching, and finally the photoresist is removed to obtain a VO2 super surface layer, thereby completing a preparation method for a near-infrared shielding thermochromic smart window.

[0044] This implementation first uses DC magnetron sputtering to alternately deposit oxide thin films and highly reflective metal films on a cleaned quartz substrate to construct a hyperbolic metamaterial structure. Next, DC sputtering is used to deposit a thicker oxide film on the hyperbolic metamaterial structure, serving as the dielectric layer of the Fabry-Perot resonant cavity. Next, high-energy pulsed magnetron sputtering combined with post-annealing is used to deposit a tungsten (W)-doped vanadium dioxide (VO2) film as the phase change functional layer. Finally, ultraviolet lithography and reactive ion etching are combined to fabricate the VO2 metasurface structure.

[0045] Specific embodiment 7: This embodiment differs from specific embodiment 6 in that: in steps 2 and 3, DC magnetron sputtering technology is used to deposit the first oxide dielectric layer or the second oxide dielectric layer at a temperature of 100°C to 200°C; in step 2, DC magnetron sputtering technology is used to deposit the metal reflective layer at a temperature of 50°C to 100°C, a power of 80W to 120W, and a deposition pressure of 0.6Pa to 0.8Pa. Other aspects are the same as specific embodiment 6.

[0046] Specific embodiment 8: This embodiment differs from either specific embodiment 6 or 7 in that, in step 4, high-energy pulsed magnetron sputtering technology is employed. A vanadium-tungsten alloy target is used to deposit a VO2 layer on the first oxide dielectric layer at a power of 180W to 220W, an argon to oxygen flow ratio of 80 sccm:(0.8 sccm to 1.4 sccm), and a temperature of 300°C to 400°C. Other steps are the same as those in specific embodiment 6 or 7.

[0047] Specific embodiment 9: This embodiment differs from specific embodiments 6 to 8 in that the post-annealing treatment described in step 4 is performed at a temperature of 350° C. to 400° C. and an argon gas flow rate of 100 sccm to 120 sccm for 0.5 to 3 hours. Other aspects are the same as specific embodiments 6 to 8.

[0048] Specific embodiment 10: This embodiment differs from specific embodiments 6 to 9 in that: in step 4, a layer of photoresist is coated on the VO2 layer of the planar multilayer film structure, pre-baked at a temperature of 120°C to 150°C for 2 minutes to 3.5 minutes, and selectively exposed to light for 25 seconds to 60 seconds using ultraviolet photolithography. Then, the photoresist is post-baked at a temperature of 100°C to 150°C for 1.5 minutes to 2.5 minutes, followed by development for 5 seconds to 15 seconds, and finally etched for 20 seconds to 60 seconds using reactive ion beam etching technology. Finally, the photoresist is removed. Other steps are the same as specific embodiments 6 to 9.

[0049] The following examples are used to verify the beneficial effects of the present invention:

[0050] Example 1:

[0051] A near-infrared shielding thermochromic smart window, which consists of a substrate, a hyperbolic metamaterial structure, a first oxide dielectric layer and a VO2 metasurface layer from bottom to top;

[0052] The hyperbolic metamaterial structure is a four-layer structure consisting of a second oxide dielectric layer and a metal reflective layer alternately arranged from bottom to top;

[0053] The VO2 super surface layer is composed of a plurality of W-doped VO2 micro-nano structural units, each of which is square in shape and has a side length of 4 μm. A rectangular array of the plurality of W-doped VO2 micro-nano structural units is arranged on the surface of the first oxide dielectric layer, with a surface coverage of 0.79 and a distance between adjacent W-doped VO2 micro-nano structural units of 0.5 μm.

[0054] In the W-doped VO2 micro-nanostructure unit, W accounts for 2% of the total number of W and V atoms.

[0055] The substrate is quartz glass.

[0056] The material of the first oxide dielectric layer is ZrO2;

[0057] The material of the second oxide dielectric layer is SiO2.

[0058] The material of the metal reflective layer is Ag.

[0059] The thickness of the first oxide dielectric layer is 500 nm; the thickness of the second oxide dielectric layer is 110 nm; the thickness of the metal reflective layer is 10 nm; and the thickness of the VO2 super surface layer is 60 nm.

[0060] The method for preparing the above-mentioned near-infrared shielding thermochromic smart window is carried out according to the following steps:

[0061] 1. Clean the substrate:

[0062] The substrate is cleaned using analytically pure anhydrous ethanol and ultrapure water as cleaning agents, and then sealed for standby use to obtain a pretreated substrate;

[0063] 2. Preparation of hyperbolic metamaterial structures:

[0064] Using DC magnetron sputtering technology, a second oxide dielectric layer and a metal reflective layer are alternately deposited on the pretreated substrate surface to form a four-layer structure, thereby obtaining a hyperbolic metamaterial structure.

[0065] Depositing the second oxide dielectric layer specifically involves using a DC magnetron sputtering technique to deposit the second oxide dielectric layer at a temperature of 200° C.;

[0066] The metal reflective layer is deposited by using a DC magnetron sputtering technique at a temperature of 50° C., a power of 80 W, and a deposition pressure of 0.6 Pa.

[0067] The hyperbolic metamaterial structure is specifically SiO2(110nm) / Ag(10nm) / SiO2(110nm) / Ag(10nm);

[0068] 3. Preparation of the first oxide dielectric layer:

[0069] Using DC magnetron sputtering technology at a temperature of 200°C, a first oxide dielectric layer is deposited on the metal reflective layer at the top of the hyperbolic metamaterial structure;

[0070] 4. Preparation of VO2 super surface layer:

[0071] Using high-energy pulsed magnetron sputtering technology, under the conditions of power of 180W, flow ratio of argon to oxygen of 80sccm:1.4sccm and temperature of 300℃, a vanadium-tungsten alloy target was used to deposit a VO2 layer on the first oxide dielectric layer. Then, at a temperature of 400℃ and an argon flow rate of 100sccm, annealing was carried out for 3h to obtain a planar multilayer film structure. A layer of photoresist was coated on the VO2 layer of the planar multilayer film structure, pre-baked at a temperature of 120℃ for 3.5min, and selectively exposed to the photoresist for 60s using ultraviolet photolithography technology. Then, post-baked at a temperature of 100℃ for 2.5min, developed for 15s, and etched for 60s using reactive ion beam etching technology. Finally, the photoresist was removed to obtain a VO2 super surface layer, thus completing a preparation method for a near-infrared shielding thermochromic smart window.

[0072] The purity of the vanadium-tungsten alloy target is 99.9%, V:W=98:2at%; the photoresist is NRT-250P negative photoresist.

[0073] The UV-visible-near infrared spectrum and Fourier transform infrared spectrum were used to test the visible-near infrared transmission spectrum and mid- and far-infrared reflection spectrum of the coating at high temperature (H, 60℃) and low temperature (L, 0℃), and the visible transmittance ratio T at high and low temperatures was obtained by analysis and calculation. lum , average transmittance in the near-infrared band (0.8~2.5μm) Emissivity ε and emissivity change Δε in the mid- and far-infrared (2.5μm~25μm). lum (H) = 34%, T lum (L) = 29%, ε H =0.46,ε L =0.05, Δε=0.41.

[0074] Example 2:

[0075] A near-infrared shielding thermochromic smart window, which consists of a substrate, a hyperbolic metamaterial structure, a first oxide dielectric layer and a VO2 metasurface layer from bottom to top;

[0076] The hyperbolic metamaterial structure is a four-layer structure consisting of a second oxide dielectric layer and a metal reflective layer alternately arranged from bottom to top;

[0077] The VO2 super surface layer is composed of a plurality of W-doped VO2 micro-nano structural units, each of which is square in shape and has a side length of 4 μm. A rectangular array of the plurality of W-doped VO2 micro-nano structural units is arranged on the surface of the first oxide dielectric layer, with a surface coverage of 0.79 and a distance between adjacent W-doped VO2 micro-nano structural units of 0.5 μm.

[0078] In the W-doped VO2 micro-nanostructure unit, W accounts for 2% of the total number of W and V atoms.

[0079] The substrate is quartz glass.

[0080] The material of the first oxide dielectric layer is HfO2;

[0081] The material of the second oxide dielectric layer is SiO2.

[0082] The material of the metal reflective layer is Ag.

[0083] The thickness of the first oxide dielectric layer is 700 nm; the thickness of the second oxide dielectric layer is 110 nm; the thickness of the metal reflective layer is 12 nm; and the thickness of the VO2 super surface layer is 50 nm.

[0084] The method for preparing the above-mentioned near-infrared shielding thermochromic smart window is carried out according to the following steps:

[0085] 1. Clean the substrate:

[0086] The substrate is cleaned using analytically pure anhydrous ethanol and ultrapure water as cleaning agents, and then sealed for standby use to obtain a pretreated substrate;

[0087] 2. Preparation of hyperbolic metamaterial structures:

[0088] Using DC magnetron sputtering technology, a second oxide dielectric layer and a metal reflective layer are alternately deposited on the pretreated substrate surface to form a four-layer structure, thereby obtaining a hyperbolic metamaterial structure.

[0089] Depositing the second oxide dielectric layer specifically involves using a DC magnetron sputtering technique to deposit the second oxide dielectric layer at a temperature of 200° C.;

[0090] The metal reflective layer is deposited by using a DC magnetron sputtering technique at a temperature of 50° C., a power of 80 W, and a deposition pressure of 0.6 Pa.

[0091] The hyperbolic metamaterial structure is specifically SiO2(110nm) / Ag(12nm) / SiO2(110nm) / Ag(12nm);

[0092] 3. Preparation of the first oxide dielectric layer:

[0093] Using DC magnetron sputtering technology at a temperature of 100°C, a first oxide dielectric layer is deposited on the metal reflective layer on the top layer of the hyperbolic metamaterial structure;

[0094] 4. Preparation of VO2 super surface layer:

[0095] Using high-energy pulse magnetron sputtering technology, under the conditions of power of 200W, flow ratio of argon to oxygen of 80sccm:1.2sccm and temperature of 350℃, a vanadium-tungsten alloy target was used to deposit a VO2 layer on the first oxide dielectric layer. Then, at a temperature of 400℃ and an argon flow rate of 110sccm, annealing was carried out for 2h to obtain a planar multilayer film structure. A layer of photoresist was coated on the VO2 layer of the planar multilayer film structure, pre-baked at a temperature of 130℃ for 3min, and the photoresist was selectively exposed for 50s using ultraviolet photolithography technology. Then, at a temperature of 125℃, it was post-baked for 2min, developed for 10s, and etched for 45s using reactive ion beam etching technology. Finally, the photoresist was removed to obtain a VO2 super surface layer, thus completing a preparation method for a near-infrared shielding thermochromic smart window.

[0096] The purity of the vanadium-tungsten alloy target is 99.9%, V:W=98:2at%; the photoresist is NRT-250P negative photoresist.

[0097] The UV-visible-near infrared spectrum and Fourier transform infrared spectrum were used to test the visible-near infrared transmission spectrum and mid- and far-infrared reflection spectrum of the coating at high temperature (H, 60℃) and low temperature (L, 0℃), and the visible transmittance ratio T at high and low temperatures was obtained by analysis and calculation. lum , average transmittance in the near-infrared band (0.8~2.5μm) Emissivity ε and emissivity change Δε in the mid- and far-infrared (2.5μm~25μm). lum (H) = 33%, T lum (L) = 28%, ε H =0.51,ε L =0.05, Δε=0.46.

[0098] Example 3:

[0099] A near-infrared shielding thermochromic smart window, which consists of a substrate, a hyperbolic metamaterial structure, a first oxide dielectric layer and a VO2 metasurface layer from bottom to top;

[0100] The hyperbolic metamaterial structure is a four-layer structure consisting of a second oxide dielectric layer and a metal reflective layer alternately arranged from bottom to top;

[0101] The VO2 super surface layer is composed of a plurality of W-doped VO2 micro-nano structural units, each of which is square in shape and has a side length of 3.5 μm. A rectangular array of the plurality of W-doped VO2 micro-nano structural units is arranged on the surface of the first oxide dielectric layer, with a surface coverage of 0.77, and a distance between adjacent W-doped VO2 micro-nano structural units of 0.5 μm.

[0102] In the W-doped VO2 micro-nanostructure unit, W accounts for 2% of the total number of W and V atoms.

[0103] The substrate is quartz glass.

[0104] The material of the first oxide dielectric layer is HfO2;

[0105] The material of the second oxide dielectric layer is SiO2.

[0106] The material of the metal reflective layer is Ag.

[0107] The thickness of the first oxide dielectric layer is 700 nm; the thickness of the second oxide dielectric layer is 110 nm; the thickness of the metal reflective layer is 15 nm; and the thickness of the VO2 super surface layer is 50 nm.

[0108] The method for preparing the above-mentioned near-infrared shielding thermochromic smart window is carried out according to the following steps:

[0109] 1. Clean the substrate:

[0110] The substrate is cleaned using analytically pure anhydrous ethanol and ultrapure water as cleaning agents, and then sealed for standby use to obtain a pretreated substrate;

[0111] 2. Preparation of hyperbolic metamaterial structures:

[0112] Using DC magnetron sputtering technology, a second oxide dielectric layer and a metal reflective layer are alternately deposited on the pretreated substrate surface to form a four-layer structure, thereby obtaining a hyperbolic metamaterial structure.

[0113] Depositing the second oxide dielectric layer specifically involves using a DC magnetron sputtering technique to deposit the second oxide dielectric layer at a temperature of 200° C.;

[0114] The metal reflective layer is deposited by using a DC magnetron sputtering technique at a temperature of 50° C., a power of 80 W, and a deposition pressure of 0.6 Pa.

[0115] The hyperbolic metamaterial structure is specifically SiO2(110nm) / Ag(15nm) / SiO2(110nm) / Ag(15nm);

[0116] 3. Preparation of the first oxide dielectric layer:

[0117] Using DC magnetron sputtering technology at a temperature of 100°C, a first oxide dielectric layer is deposited on the metal reflective layer on the top layer of the hyperbolic metamaterial structure;

[0118] 4. Preparation of VO2 super surface layer:

[0119] Using high-energy pulsed magnetron sputtering technology, under the conditions of power of 220W, flow ratio of argon to oxygen of 80sccm:1.0sccm and temperature of 400℃, a vanadium-tungsten alloy target was used to deposit a VO2 layer on the first oxide dielectric layer. Then, at a temperature of 400℃ and an argon flow rate of 120sccm, annealing was carried out for 1h to obtain a planar multilayer film structure. A layer of photoresist was coated on the VO2 layer of the planar multilayer film structure, pre-baked at a temperature of 140℃ for 2.5min, and selectively exposed to the photoresist for 40s using ultraviolet photolithography technology. Then, post-baked at a temperature of 150℃ for 1.5min, developed for 5s, and etched for 45s using reactive ion beam etching technology. Finally, the photoresist was removed to obtain a VO2 super surface layer, thus completing a preparation method for a near-infrared shielding thermochromic smart window.

[0120] The purity of the vanadium-tungsten alloy target is 99.9%, V:W=98:2at%; the photoresist is NRT-250P negative photoresist.

[0121] The UV-visible-near infrared spectrum and Fourier transform infrared spectrum were used to test the visible-near infrared transmission spectrum and mid- and far-infrared reflection spectrum of the coating at high temperature (H, 60℃) and low temperature (L, 0℃), and the visible transmittance ratio T at high and low temperatures was obtained by analysis and calculation. lum , average transmittance in the near-infrared band (0.8~2.5μm) Emissivity ε and emissivity change Δε in the mid- and far-infrared (2.5μm~25μm). lum (H) = 40%, T lum (L) = 38%, ε H =0.52,ε L =0.10, Δε=0.42.

[0122] Example 4:

[0123] A near-infrared shielding thermochromic smart window, which consists of a substrate, a hyperbolic metamaterial structure, a first oxide dielectric layer and a VO2 metasurface layer from bottom to top;

[0124] The hyperbolic metamaterial structure is a four-layer structure consisting of a second oxide dielectric layer and a metal reflective layer alternately arranged from bottom to top;

[0125] The VO2 super surface layer is composed of a plurality of W-doped VO2 micro-nano structural units, each of which is square in shape and has a side length of 1.5 μm. A rectangular array of the plurality of W-doped VO2 micro-nano structural units is arranged on the surface of the first oxide dielectric layer, with a surface coverage of 0.56, and a distance between adjacent W-doped VO2 micro-nano structural units of 0.5 μm.

[0126] In the W-doped VO2 micro-nanostructure unit, W accounts for 2% of the total number of W and V atoms.

[0127] The substrate is quartz glass.

[0128] The material of the first oxide dielectric layer is HfO2;

[0129] The material of the second oxide dielectric layer is ZrO2.

[0130] The material of the metal reflective layer is Ag.

[0131] The thickness of the first oxide dielectric layer is 900 nm; the thickness of the second oxide dielectric layer is 120 nm; the thickness of the metal reflective layer is 18 nm; and the thickness of the VO2 super surface layer is 40 nm.

[0132] The method for preparing the above-mentioned near-infrared shielding thermochromic smart window is carried out according to the following steps:

[0133] 1. Clean the substrate:

[0134] The substrate is cleaned using analytically pure anhydrous ethanol and ultrapure water as cleaning agents, and then sealed for standby use to obtain a pretreated substrate;

[0135] 2. Preparation of hyperbolic metamaterial structures:

[0136] Using DC magnetron sputtering technology, a second oxide dielectric layer and a metal reflective layer are alternately deposited on the pretreated substrate surface to form a four-layer structure, thereby obtaining a hyperbolic metamaterial structure.

[0137] Depositing the second oxide dielectric layer specifically involves using a DC magnetron sputtering technique to deposit the second oxide dielectric layer at a temperature of 200° C.;

[0138] The metal reflective layer is deposited by using a DC magnetron sputtering technique at a temperature of 50° C., a power of 80 W, and a deposition pressure of 0.6 Pa.

[0139] The hyperbolic metamaterial structure is specifically ZrO2(120nm) / Ag(18nm) / ZrO2(120nm) / Ag(18nm);

[0140] 3. Preparation of the first oxide dielectric layer:

[0141] Using DC magnetron sputtering technology at a temperature of 100°C, a first oxide dielectric layer is deposited on the metal reflective layer on the top layer of the hyperbolic metamaterial structure;

[0142] 4. Preparation of VO2 super surface layer:

[0143] Using high-energy pulse magnetron sputtering technology, under the conditions of power of 240W, flow ratio of argon to oxygen of 80sccm:0.8sccm and temperature of 400℃, a vanadium-tungsten alloy target was used to deposit a VO2 layer on the first oxide dielectric layer, and then annealed for 0.5h at a temperature of 400℃ and an argon flow rate of 120sccm to obtain a planar multilayer film structure. A layer of photoresist was coated on the VO2 layer of the planar multilayer film structure, pre-baked at a temperature of 150℃ for 2min, and selectively exposed to the photoresist for 30s using ultraviolet photolithography technology, and then post-baked at a temperature of 125℃ for 2min, developed for 10s, and etched for 30s using reactive ion beam etching technology. Finally, the photoresist was removed to obtain a VO2 super surface layer, thus completing a preparation method for a near-infrared shielding thermochromic smart window.

[0144] The purity of the vanadium-tungsten alloy target is 99.9%, V:W=98:2at%; the photoresist is NRT-250P negative photoresist.

[0145] The UV-visible-near infrared spectrum and Fourier transform infrared spectrum were used to test the visible-near infrared transmission spectrum and mid- and far-infrared reflection spectrum of the coating at high temperature (H, 60℃) and low temperature (L, 0℃), and the visible transmittance ratio T at high and low temperatures was obtained by analysis and calculation. lum , average transmittance in the near-infrared band (0.8~2.5μm) Emissivity ε and emissivity change Δε in the mid- and far-infrared (2.5μm~25μm). lum (H) = 52%, T lum (L) = 42%, ε H =0.53,ε L =0.10, Δε=0.43.

[0146] Embodiment 5:

[0147] A near-infrared shielding thermochromic smart window, which consists of a substrate, a hyperbolic metamaterial structure, a first oxide dielectric layer and a VO2 metasurface layer from bottom to top;

[0148] The hyperbolic metamaterial structure is a four-layer structure consisting of a second oxide dielectric layer and a metal reflective layer alternately arranged from bottom to top;

[0149] The VO2 super surface layer is composed of a plurality of W-doped VO2 micro-nano structural units, each of which is square in shape and has a side length of 2 μm. A rectangular array of the plurality of W-doped VO2 micro-nano structural units is arranged on the surface of the first oxide dielectric layer, with a surface coverage of 0.64 and a distance between adjacent W-doped VO2 micro-nano structural units of 0.5 μm.

[0150] In the W-doped VO2 micro-nanostructure unit, W accounts for 2% of the total number of W and V atoms.

[0151] The substrate is quartz glass.

[0152] The material of the first oxide dielectric layer is HfO2;

[0153] The material of the second oxide dielectric layer is ZrO2.

[0154] The material of the metal reflective layer is Ag.

[0155] The thickness of the first oxide dielectric layer is 1100 nm; the thickness of the second oxide dielectric layer is 115 nm; the thickness of the metal reflective layer is 12 nm; and the thickness of the VO2 super surface layer is 20 nm.

[0156] The method for preparing the above-mentioned near-infrared shielding thermochromic smart window is carried out according to the following steps:

[0157] 1. Clean the substrate:

[0158] The substrate is cleaned using analytically pure anhydrous ethanol and ultrapure water as cleaning agents, and then sealed for standby use to obtain a pretreated substrate;

[0159] 2. Preparation of hyperbolic metamaterial structures:

[0160] Using DC magnetron sputtering technology, a second oxide dielectric layer and a metal reflective layer are alternately deposited on the pretreated substrate surface to form a four-layer structure, thereby obtaining a hyperbolic metamaterial structure.

[0161] Depositing the second oxide dielectric layer specifically involves using a DC magnetron sputtering technique to deposit the second oxide dielectric layer at a temperature of 200° C.;

[0162] The metal reflective layer is deposited by using a DC magnetron sputtering technique at a temperature of 50° C., a power of 80 W, and a deposition pressure of 0.6 Pa.

[0163] The hyperbolic metamaterial structure is specifically ZrO2(115nm) / Ag(12nm) / ZrO2(115nm) / Ag(12nm);

[0164] 3. Preparation of the first oxide dielectric layer:

[0165] Using DC magnetron sputtering technology at a temperature of 100°C, a first oxide dielectric layer is deposited on the metal reflective layer on the top layer of the hyperbolic metamaterial structure;

[0166] 4. Preparation of VO2 super surface layer:

[0167] High-energy pulsed magnetron sputtering technology is used. Under the conditions of power of 220W, flow ratio of argon to oxygen of 80sccm:1.0sccm and temperature of 400℃, a vanadium-tungsten alloy target is used to deposit a VO2 layer on the first oxide dielectric layer. Then, at a temperature of 400℃ and an argon flow rate of 120sccm, annealing is carried out for 1h to obtain a planar multilayer film structure. A layer of photoresist is coated on the VO2 layer of the planar multilayer film structure, pre-baked at a temperature of 150℃ for 2min, and the photoresist is selectively exposed for 25s using ultraviolet photolithography technology. Then, post-baked at a temperature of 125℃ for 2min, developed for 10s, and etched for 20s using reactive ion beam etching technology. Finally, the photoresist is removed to obtain a VO2 super surface layer, thereby completing a preparation method for a near-infrared shielding thermochromic smart window.

[0168] The purity of the vanadium-tungsten alloy target is 99.9%, V:W=98:2at%; the photoresist is NRT-250P negative photoresist.

[0169] The UV-visible-near infrared spectrum and Fourier transform infrared spectrum were used to test the visible-near infrared transmission spectrum and mid- and far-infrared reflection spectrum of the coating at high temperature (H, 60℃) and low temperature (L, 0℃), and the visible transmittance ratio T at high and low temperatures was obtained by analysis and calculation. lum , average transmittance in the near-infrared band (0.8~2.5μm) Emissivity ε and emissivity change Δε in the mid- and far-infrared (2.5μm~25μm). lum (H) = 49%, T lum (L) = 42%, ε H =0.58,ε L =0.11, Δε=0.47.

[0170] Example 6:

[0171] A near-infrared shielding thermochromic smart window, which consists of a substrate, a hyperbolic metamaterial structure, a first oxide dielectric layer and a VO2 metasurface layer from bottom to top;

[0172] The hyperbolic metamaterial structure is a four-layer structure consisting of a second oxide dielectric layer and a metal reflective layer alternately arranged from bottom to top;

[0173] The VO2 super surface layer is composed of a plurality of W-doped VO2 micro-nano structural units, each of which is square in shape and has a side length of 3.5 μm. A rectangular array of the plurality of W-doped VO2 micro-nano structural units is arranged on the surface of the first oxide dielectric layer, with a surface coverage of 0.60, and a distance between adjacent W-doped VO2 micro-nano structural units of 1 μm.

[0174] In the W-doped VO2 micro-nanostructure unit, W accounts for 2% of the total number of W and V atoms.

[0175] The substrate is quartz glass.

[0176] The material of the first oxide dielectric layer is TiO2;

[0177] The material of the second oxide dielectric layer is SiO2.

[0178] The material of the metal reflective layer is Au.

[0179] The thickness of the first oxide dielectric layer is 1100 nm; the thickness of the second oxide dielectric layer is 120 nm; the thickness of the metal reflective layer is 10 nm; and the thickness of the VO2 super surface layer is 20 nm.

[0180] The method for preparing the above-mentioned near-infrared shielding thermochromic smart window is carried out according to the following steps:

[0181] 1. Clean the substrate:

[0182] The substrate is cleaned using analytically pure anhydrous ethanol and ultrapure water as cleaning agents, and then sealed for standby use to obtain a pretreated substrate;

[0183] 2. Preparation of hyperbolic metamaterial structures:

[0184] Using DC magnetron sputtering technology, a second oxide dielectric layer and a metal reflective layer are alternately deposited on the pretreated substrate surface to form a four-layer structure, thereby obtaining a hyperbolic metamaterial structure.

[0185] Depositing the second oxide dielectric layer specifically involves using a DC magnetron sputtering technique to deposit the second oxide dielectric layer at a temperature of 200° C.;

[0186] The metal reflective layer is deposited by using a DC magnetron sputtering technique at a temperature of 100° C., a power of 120 W, and a deposition pressure of 0.8 Pa.

[0187] The hyperbolic metamaterial structure is specifically SiO2(120nm) / Au(10nm) / SiO2(120nm) / Au(10nm);

[0188] 3. Preparation of the first oxide dielectric layer:

[0189] Using DC magnetron sputtering technology at a temperature of 200°C, a first oxide dielectric layer is deposited on the metal reflective layer at the top of the hyperbolic metamaterial structure;

[0190] 4. Preparation of VO2 super surface layer:

[0191] High-energy pulsed magnetron sputtering technology is used. Under the conditions of power of 220W, flow ratio of argon to oxygen of 80sccm:1.0sccm and temperature of 400℃, a vanadium-tungsten alloy target is used to deposit a VO2 layer on the first oxide dielectric layer. Then, at a temperature of 400℃ and an argon flow rate of 120sccm, annealing is carried out for 1h to obtain a planar multilayer film structure. A layer of photoresist is coated on the VO2 layer of the planar multilayer film structure, pre-baked at a temperature of 150℃ for 2min, and the photoresist is selectively exposed for 25s using ultraviolet photolithography technology. Then, post-baked at a temperature of 125℃ for 2min, developed for 10s, and etched for 20s using reactive ion beam etching technology. Finally, the photoresist is removed to obtain a VO2 super surface layer, thereby completing a preparation method for a near-infrared shielding thermochromic smart window.

[0192] The purity of the vanadium-tungsten alloy target is 99.9%, V:W=98:2at%; the photoresist is NRT-250P negative photoresist.

[0193] The UV-visible-near infrared spectrum and Fourier transform infrared spectrum were used to test the visible-near infrared transmission spectrum and mid- and far-infrared reflection spectrum of the coating at high temperature (H, 60℃) and low temperature (L, 0℃), and the visible transmittance ratio T at high and low temperatures was obtained by analysis and calculation. lum , average transmittance in the near-infrared band (0.8~2.5μm) Emissivity ε and emissivity change Δε in the mid- and far-infrared (2.5μm~25μm). lum (H) = 54%, T lum (L) = 44%, ε H =0.60,ε L =0.12, Δε=0.48.

[0194] Embodiment seven:

[0195] A near-infrared shielding thermochromic smart window, which consists of a substrate, a hyperbolic metamaterial structure, a first oxide dielectric layer and a VO2 metasurface layer from bottom to top;

[0196] The hyperbolic metamaterial structure is a four-layer structure consisting of a second oxide dielectric layer and a metal reflective layer alternately arranged from bottom to top;

[0197] The VO2 super surface layer is composed of a plurality of W-doped VO2 micro-nano structural units, each of which is square in shape and has a side length of 4 μm. A rectangular array of the plurality of W-doped VO2 micro-nano structural units is arranged on the surface of the first oxide dielectric layer, with a surface coverage of 0.79 and a distance between adjacent W-doped VO2 micro-nano structural units of 0.5 μm.

[0198] In the W-doped VO2 micro-nanostructure unit, W accounts for 2% of the total number of W and V atoms.

[0199] The substrate is quartz glass.

[0200] The material of the first oxide dielectric layer is Al2O3;

[0201] The material of the second oxide dielectric layer is SiO2.

[0202] The material of the metal reflective layer is Au.

[0203] The thickness of the first oxide dielectric layer is 1200 nm; the thickness of the second oxide dielectric layer is 140 nm; the thickness of the metal reflective layer is 12 nm; and the thickness of the VO2 super surface layer is 20 nm.

[0204] The method for preparing the above-mentioned near-infrared shielding thermochromic smart window is carried out according to the following steps:

[0205] 1. Clean the substrate:

[0206] The substrate is cleaned using analytically pure anhydrous ethanol and ultrapure water as cleaning agents, and then sealed for standby use to obtain a pretreated substrate;

[0207] 2. Preparation of hyperbolic metamaterial structures:

[0208] Using DC magnetron sputtering technology, a second oxide dielectric layer and a metal reflective layer are alternately deposited on the pretreated substrate surface to form a four-layer structure, thereby obtaining a hyperbolic metamaterial structure.

[0209] Depositing the second oxide dielectric layer specifically involves using a DC magnetron sputtering technique to deposit the second oxide dielectric layer at a temperature of 200° C.;

[0210] The metal reflective layer is deposited by using a DC magnetron sputtering technique at a temperature of 100° C., a power of 120 W, and a deposition pressure of 0.8 Pa.

[0211] The hyperbolic metamaterial structure is specifically SiO2(140nm) / Au(12nm) / SiO2(140nm) / Au(12nm);

[0212] 3. Preparation of the first oxide dielectric layer:

[0213] Using DC magnetron sputtering technology at a temperature of 200°C, a first oxide dielectric layer is deposited on the metal reflective layer at the top of the hyperbolic metamaterial structure;

[0214] 4. Preparation of VO2 super surface layer:

[0215] High-energy pulsed magnetron sputtering technology is used. Under the conditions of power of 220W, flow ratio of argon to oxygen of 80sccm:1.0sccm and temperature of 400℃, a vanadium-tungsten alloy target is used to deposit a VO2 layer on the first oxide dielectric layer. Then, at a temperature of 400℃ and an argon flow rate of 120sccm, annealing is carried out for 1h to obtain a planar multilayer film structure. A layer of photoresist is coated on the VO2 layer of the planar multilayer film structure, pre-baked at a temperature of 150℃ for 2min, and the photoresist is selectively exposed for 25s using ultraviolet photolithography technology. Then, post-baked at a temperature of 125℃ for 2min, developed for 10s, and etched for 20s using reactive ion beam etching technology. Finally, the photoresist is removed to obtain a VO2 super surface layer, thereby completing a preparation method for a near-infrared shielding thermochromic smart window.

[0216] The purity of the vanadium-tungsten alloy target is 99.9%, V:W=98:2at%; the photoresist is NRT-250P negative photoresist.

[0217] The UV-visible-near infrared spectrum and Fourier transform infrared spectrum were used to test the visible-near infrared transmission spectrum and mid- and far-infrared reflection spectrum of the coating at high temperature (H, 60℃) and low temperature (L, 0℃), and the visible transmittance ratio T at high and low temperatures was obtained by analysis and calculation. lum , average transmittance in the near-infrared band (0.8~2.5μm) Emissivity ε and emissivity change Δε in the mid- and far-infrared (2.5μm~25μm). lum (H) = 45%, T lum (L) = 39%, ε H =0.68,ε L =0.14, Δε=0.54.

[0218] Embodiment 8:

[0219] A near-infrared shielding thermochromic smart window, which consists of a substrate, a hyperbolic metamaterial structure, a first oxide dielectric layer and a VO2 metasurface layer from bottom to top;

[0220] The hyperbolic metamaterial structure is a four-layer structure consisting of a second oxide dielectric layer and a metal reflective layer alternately arranged from bottom to top;

[0221] The VO2 super surface layer is composed of a plurality of W-doped VO2 micro-nano structural units, each of which is square in shape and has a side length of 4.5 μm. A rectangular array of the plurality of W-doped VO2 micro-nano structural units is arranged on the surface of the first oxide dielectric layer, with a surface coverage of 0.81, and a distance between adjacent W-doped VO2 micro-nano structural units of 0.5 μm.

[0222] In the W-doped VO2 micro-nanostructure unit, W accounts for 2% of the total number of W and V atoms.

[0223] The substrate is quartz glass.

[0224] The material of the first oxide dielectric layer is SiO2;

[0225] The material of the second oxide dielectric layer is TiO2.

[0226] The material of the metal reflective layer is Au.

[0227] The thickness of the first oxide dielectric layer is 1300 nm; the thickness of the second oxide dielectric layer is 150 nm; the thickness of the metal reflective layer is 12 nm; and the thickness of the VO2 super surface layer is 20 nm.

[0228] The method for preparing the above-mentioned near-infrared shielding thermochromic smart window is carried out according to the following steps:

[0229] 1. Clean the substrate:

[0230] The substrate is cleaned using analytically pure anhydrous ethanol and ultrapure water as cleaning agents, and then sealed for standby use to obtain a pretreated substrate;

[0231] 2. Preparation of hyperbolic metamaterial structures:

[0232] A second oxide dielectric layer and a metal reflective layer are alternately deposited on the pretreated substrate surface using DC magnetron sputtering technology to form a four-layer structure, thereby obtaining a hyperbolic metamaterial structure.

[0233] Depositing the second oxide dielectric layer specifically involves using a DC magnetron sputtering technique to deposit the second oxide dielectric layer at a temperature of 200° C.;

[0234] The metal reflective layer is deposited by using a DC magnetron sputtering technique at a temperature of 100° C., a power of 120 W, and a deposition pressure of 0.8 Pa.

[0235] The hyperbolic metamaterial structure is specifically TiO2(150nm) / Au(12nm) / TiO2(150nm) / Au(12nm);

[0236] 3. Preparation of the first oxide dielectric layer:

[0237] Using DC magnetron sputtering technology at a temperature of 200°C, a first oxide dielectric layer is deposited on the metal reflective layer at the top of the hyperbolic metamaterial structure;

[0238] 4. Preparation of VO2 super surface layer:

[0239] Using high-energy pulse magnetron sputtering technology, a VO2 layer was deposited on the first oxide dielectric layer using a vanadium-tungsten alloy target at a power of 220W, an argon to oxygen flow ratio of 80sccm:1.0sccm and a temperature of 400°C. Then, annealing was performed for 1h at a temperature of 350°C and an argon flow rate of 120sccm to obtain a planar multilayer film structure. A layer of photoresist was coated on the VO2 layer of the planar multilayer film structure, pre-baked at a temperature of 150°C for 2min, and selectively exposed to the photoresist for 25s using ultraviolet photolithography technology. Then, post-baked at a temperature of 125°C for 2min, developed for 10s, and etched for 20s using reactive ion beam etching technology. Finally, the photoresist was removed to obtain a VO2 super surface layer, thereby completing a preparation method for a near-infrared shielding thermochromic smart window.

[0240] The purity of the vanadium-tungsten alloy target is 99.9%, V:W=98:2at%; the photoresist is NRT-250P negative photoresist.

[0241] The UV-visible-near infrared spectrum and Fourier transform infrared spectrum were used to test the visible-near infrared transmission spectrum and mid- and far-infrared reflection spectrum of the coating at high temperature (H, 60℃) and low temperature (L, 0℃), and the visible transmittance ratio T at high and low temperatures was obtained by analysis and calculation. lum , average transmittance in the near-infrared band (0.8~2.5μm) Emissivity ε and emissivity change Δε in the mid- and far-infrared (2.5μm~25μm). lum (H) = 46%, T lum (L) = 40%, ε H =0.73,ε L =0.23, Δε=0.50.

Claims

1. A near-infrared shielding thermochromic smart window, characterized in that It consists of a substrate, a hyperbolic metamaterial structure, a first oxide dielectric layer, and a VO2 super surface layer from bottom to top; The hyperbolic metamaterial structure is a four-layer structure consisting of a second oxide dielectric layer and a metal reflective layer alternately arranged from bottom to top; The VO2 super surface layer is composed of a plurality of W-doped VO2 micro-nano structural units, the shape of the W-doped VO2 micro-nano structural units is a square, and the side length of the square is 1.5μm to 4.5μm; a plurality of W-doped VO2 micro-nano structural unit arrays are arranged on the surface of the first oxide dielectric layer, the surface coverage is 0.56 to 0.81, and the distance between adjacent W-doped VO2 micro-nano structural units is 0.5μm to 1μm; In the W-doped VO2 micro-nano structure unit, W accounts for 2% of the total number of W and V atoms.

2. The near-infrared shielding thermochromic smart window according to claim 1, characterized in that The substrate is quartz glass.

3. The near-infrared shielding thermochromic smart window according to claim 1, characterized in that The material of the first oxide dielectric layer and the second oxide dielectric layer is SiO2, ZrO2, HfO2, TiO2 or Al2O3.

4. The near-infrared shielding thermochromic smart window according to claim 1, characterized in that The material of the metal reflective layer is Ag or Au.

5. The near-infrared shielding thermochromic smart window according to claim 1, characterized in that The thickness of the first oxide dielectric layer is 500nm to 1300nm; the thickness of the second oxide dielectric layer is 100nm to 150nm; the thickness of the metal reflective layer is 10nm to 18nm; and the thickness of the VO2 super surface layer is 20nm to 60nm.

6. The method for preparing a near-infrared shielding thermochromic smart window according to claim 1, characterized in that It is carried out in the following steps:

1. Clean the base: Cleaning the substrate to obtain a pretreated substrate; 2. Preparation of hyperbolic metamaterial structure: Using direct current magnetron sputtering technology, a second oxide dielectric layer and a metal reflective layer are alternately deposited on the pretreated substrate surface to form a four-layer structure, thereby obtaining a hyperbolic metamaterial structure; 3. Preparation of the first oxide dielectric layer: Using direct current magnetron sputtering technology, a first oxide dielectric layer is deposited on the metal reflective layer at the top layer of the hyperbolic metamaterial structure; 4. Preparation of VO2 super surface layer: A VO2 layer is deposited on the first oxide dielectric layer by high-energy pulsed magnetron sputtering technology, and then a post-annealing treatment is performed to obtain a planar multilayer film structure. A layer of photoresist is coated on the VO2 layer of the planar multilayer film structure and pre-baked. The photoresist is selectively exposed using ultraviolet photolithography technology, and then post-baked and developed. Reactive ion beam etching technology is then used for etching, and finally the photoresist is removed to obtain a VO2 super surface layer, thereby completing a method for preparing a near-infrared shielding thermochromic smart window.

7. The method for preparing a near-infrared shielding thermochromic smart window according to claim 6, characterized in that In step 2 and step 3, DC magnetron sputtering technology is used to deposit the first oxide dielectric layer or the second oxide dielectric layer at a temperature of 100°C to 200°C; in step 2, DC magnetron sputtering technology is used to deposit the metal reflective layer at a temperature of 50°C to 100°C, a power of 80W to 120W and a deposition pressure of 0.6Pa to 0.8Pa.

8. The method for preparing a near-infrared shielding thermochromic smart window according to claim 6, characterized in that In step 4, high-energy pulse magnetron sputtering technology is used. Under the conditions of power of 180W~220W, flow ratio of argon to oxygen of 80sccm:(0.8sccm~1.4sccm) and temperature of 300℃~400℃, a vanadium-tungsten alloy target is used to deposit a VO2 layer on the first oxide dielectric layer.

9. The method for preparing a near-infrared shielding thermochromic smart window according to claim 6, characterized in that The post-annealing treatment described in step 4 is specifically performed at a temperature of 350° C. to 400° C. and an argon gas flow rate of 100 sccm to 120 sccm for 0.5 h to 3 h.

10. The method for preparing a near-infrared shielding thermochromic smart window according to claim 6, characterized in that Step 4: Coat a layer of photoresist on the VO2 layer of the planar multilayer film structure, pre-bake for 2min to 3.5min at a temperature of 120℃ to 150℃, selectively expose the photoresist for 25s to 60s using ultraviolet photolithography technology, and then post-bake for 1.5min to 2.5min at a temperature of 100℃ to 150℃, then develop for 5s to 15s, etch for 20s to 60s using reactive ion beam etching technology, and finally remove the photoresist.

Citation Information

Patent Citations

  • Tungsten-doped vanadium dioxide thermochromism film and preparation method thereof

    CN107188426A

  • Moth-eye-structure-imitated vanadium dioxide intelligent window film and preparation method thereof

    CN111139432A

  • Method Of Manufacturing Thermochromic Substrate

    US20130149441A1

  • IT8319371A0

Cited By

  • Composite glass structure and preparation method and application thereof

    CN120481400A